Isolation of mitochondrial subpopulations from skeletal muscle: Optimizing recovery and preserving integrity. (17th September 2018) - Lai, Nicola; M. Kummitha, China; Rosca, Mariana G.; Fujioka, Hisashi; Tandler, Bernard; Hoppel, Charles L.
Abstract: Aim: The subsarcolemmal (SSM) and interfibrillar (IFM) mitochondria in skeletal muscle appear to have distinct biochemical properties affecting metabolism in health and disease. The isolation of mitochondrial subpopulations has been a long‐time challenge while the presence of a continuous mitochondrial reticulum challenges the view of distinctive SSM and IFM bioenergetics. Here, a comprehensive approach is developed to identify the best conditions to separate mitochondrial fractions. Methods: The main modifications to the protocol to isolate SSM and IFM from rat skeletal muscle were: (a) decreased dispase content and homogenization speed; (b) trypsin treatment of SSM fractions; (c) recentrifugation of mitochondrial fractions at low speed to remove subcellular components. To identify the conditions preserving mitochondrial function, integrity, and maximizing their recovery, microscopy (light and electron) were used to monitor effectiveness and efficiency in separating mitochondrial subpopulations while respiratory and enzyme activities were employed to evaluate function, recovery, and integrity. Results: With the modifications described, the total mitochondrial yield increased with a recovery of 80% of mitochondria contained in the original skeletal muscle sample. The difference between SSM and IFM oxidative capacity (10%) with complex‐I substrate was significant only with a saturated ADP concentration. The inner and outer membrane damage for both subpopulations was <1% and 8%, respectively, while the respiratory control ratio was 16. Conclusion: Using a multidisciplinary approach, conditions were identified to maximize SSM and IFM recovery while preserving mitochondrial integrity, biochemistry, and morphology. High quality and recovery of mitochondrial subpopulations allow to study the relationship between these organelles and disease.